NARRATING LOCAL WISDOM IN ANDREA HIRATA’S GURU AINI: A CULTURAL STUDY THROUGH THE SOCIOLOGY OF LITERATURE AND INDIGENOUS KNOWLEDGE THEORY - Asriani, Asriani; Manugeren, M (JOURNAL OF LANGUAGE, 2025)
This study explores local wisdom in Andrea Hirata’s novel Guru Aini using a qualitative descriptive method supported by the Sociology of Literature approach and Indigenous Knowledge Theory. The research focuses on identifying and analyzing five core values of Indonesian local wisdom portrayed in the novel: mutual cooperation (gotong royong), respect for elders, simple lifestyle, love for family, and preservation of cultural traditions. These values are explored through the characters, setting, plot, and dialogue, all of which reflect the socio-cultural life of the Belitung community. The primary data source is the 2020 edition of Guru Aini, complemented by scholarly references from previous studies. The findings clearly show that all five values of local wisdom are consistently and meaningfully present throughout the novel. Each value is embedded not only in the actions and attitudes of the characters but also in the social interactions and traditions depicted in the narrative. Thus, the novel serves both as a literary text and a cultural repository, offering insight into Indonesia’s traditional knowledge systems. This research concludes that literature, particularly novels like Guru Aini, can be a powerful medium for preserving cultural identity and transmitting ethical values. The findings demonstrate that Guru Aini portrays five values of Indonesian local wisdom through narrative structure and characterization, reinforcing literature’s role as a cultural repository and educational tool for character development.